2017
DOI: 10.1177/0961203317696593
|View full text |Cite
|
Sign up to set email alerts
|

Disease evolution in late-onset and early-onset systemic lupus erythematosus

Abstract: Objective The objective of this study was to compare clinical features, disease activity, and outcome in late-onset versus early-onset systemic lupus erythematosus (SLE) over 5 years of follow up Method Patients with SLE since 1970 were followed prospectively according to standard protocol and tracked on a computerized database. Patients entering the cohort within one year of diagnosis constitute the inception cohort. Patients with late-onset (age at diagnosis ≥50) disease were identified and matched 1:2 based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 24 publications
3
49
1
3
Order By: Relevance
“…[11][12][13][14] Despite the small number of patients in the late group, this percentage of late onset is comparable to previous studies (about 15% of late-onset LN). 17 Finally, our data provides novel evidence that late-onset nephritis without other associated autoimmune diseases has comparable long-term outcomes to early-onset nephritis. This finding is most likely explained by the observation that at presentation, late-onset nephritis has clinical, laboratorial and histological features similar to early-onset nephritis.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…[11][12][13][14] Despite the small number of patients in the late group, this percentage of late onset is comparable to previous studies (about 15% of late-onset LN). 17 Finally, our data provides novel evidence that late-onset nephritis without other associated autoimmune diseases has comparable long-term outcomes to early-onset nephritis. This finding is most likely explained by the observation that at presentation, late-onset nephritis has clinical, laboratorial and histological features similar to early-onset nephritis.…”
Section: Discussionmentioning
confidence: 58%
“…Subsequent evaluation of this same cohort revealed that elderly patients have, in fact, milder activity scores. 17 A cross-sectional study also compared early-onset LN developed within 5 years (n ¼ 187) with delayedonset LN (after 5 years, n ¼ 48) and concluded that delayed LN is not uncommon and is often associated with autoimmune diseases such as Sjogren and antiphospholipid syndrome. 16 Since in these concomitant conditions the kidney is also a target organ, the nonexclusion of these patients hampers the interpretation of nephritis related exclusively to lupus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 4 , 5 ] Such result is consistent with the recent findings that earlier onset of SLE may involve more renal features. [ 10 ] However, the etiology of renal involvement in cases with coexisting SLE and HIV is difficult to determine. Renal complications due to HIV are also diverse.…”
Section: Case Reportmentioning
confidence: 99%